2013
DOI: 10.1002/dvg.22418
|View full text |Cite
|
Sign up to set email alerts
|

The C. elegans TIA‐1/TIAR homolog TIAR‐1 is required to induce germ cell apoptosis

Abstract: In Caenorhabditis elegans, physiological germ cell apoptosis eliminates more than half of the cells in the hermaphrodite gonad to support gamete quality and germline homeostasis by a still unidentified mechanism. External factors can also affect germ cell apoptosis. The BH3-only protein EGL-1 induces germ cell apoptosis when animals are exposed to pathogens or agents that produce DNA damage. DNA damage-induced apoptosis also requires the nematode p53 homolog CEP-1. Previously, we found that heat shock, oxidati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
17
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 57 publications
2
17
0
Order By: Relevance
“…S6). We could not detect expression of GFP fusions in germline due to silencing of transgenes in this tissue [74] but previous studies have shown the expression of TIAR-1 [33], [75] and TIAR-2 [32] in germ granules.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…S6). We could not detect expression of GFP fusions in germline due to silencing of transgenes in this tissue [74] but previous studies have shown the expression of TIAR-1 [33], [75] and TIAR-2 [32] in germ granules.…”
Section: Resultsmentioning
confidence: 95%
“…We assume that deletion of TIAR-1 affects only specific functions of SGs related to oxidative stress response and not to heat-shock, although it localizes to SGs formed under both conditions. Alternatively, since TIAR-1 is required to induce germ cell apoptosis under various stresses [75], the increased resistance of tiar-1 mutants to heat-shock might be related to the systemic stress response that is observed in several DNA-damage checkpoint mutants affecting programmed cell death in germline [77], [78]. In sharp contrast to tiar-1 worms, tiar-2 or tiar-3 mutants had increased mortality under heat and osmotic stress but survived as N2 under oxidative or UV-irradiation stress (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The fertility assay and embryonic lethality were done as previously described [ 32 ]. N2 and mai-2 mutants were grown at 20°C and were individually selected as L4 larvae and then transferred to new plate every 24 h over the course of 4 days.…”
Section: Methodsmentioning
confidence: 99%
“…We selected L4 animals of each strain and approximately 24 h later we mounted on slides using 2% agarose pads; the cell corpses were then visualized by fluorescence microscopy using a Nikon Eclipse E600 microscope equipped with an AxioCam MRc camera (Zeiss). For stress conditions, such as starvation, oxidative stress, heat shock and UV irradiation (DNA damage) we performed experiments as previously described [ 32 , 42 ]. To quantify apoptosis in the soma, synchronized L1 animals of N2, mai-2(xm18) and mai-2(xm19) strains grown at 20°C were fed ced-1 dsRNA until they had offspring as previously described [ 42 ].…”
Section: Methodsmentioning
confidence: 99%
“…C. elegans has three TIA-1/TIAR homologs: tiar-1 , -2 , and -3 (WormBase release WS204). Among the three homologs, tiar-1 is uniquely required for the induction of germ cell apoptosis under several stressful conditions ( Silva-García and Navarro 2013 ). tiar-1 mutant animals exhibit reduced longevity and small brood sizes and are hypersensitive to oxidative and UV stress ( Silva-García and Navarro 2013 ; Rousakis et al 2014 ).…”
mentioning
confidence: 99%